Awareness about Coronary Artery Disease (CAD) among Relatives of CAD Patients - Peter, Sanjeeth; Mashhadi, Mahpaekar; Ajith, Deva J; Pandit, Niraj; Sinha, Ravi S (National Journal of Community Medicine, 2017)
Background: The decision to modify the cardiovascular risk factors remains with the individuals and in order to modify their lifestyle, the individual should be aware and able to perceive them as ‘risk factors’. This study was conducted to determine the level of awareness among relatives of patients diagnosed to have CAD Methodology: Cross-sectional study design was used and the study population included family members of all the CAD patients attending the outpatient clinic of the hospital between the years 2011 - 2012. A total of 291 relatives participated in the study. The data collected through pilot pre-tested questionnaire. Results: Stress (92.8%) and hypertension (91.8%) were the highest aware risk factor among the family members. Awareness for non-modifiable risk factors such as age (63.2%) and family history of CAD (60.8%) was poor compare to other. A majority of the family members were aware about four symptoms of CAD such as tightening of the chest, chest pain, sweating, and shortness of breath. Conclusion: Our hypothesis that relatives of patients with known CAD would have more knowledge of risk factors was confirmed by the data and this increased awareness in the present study could be due to the fact that recently more emphasis is being given to non-communicable diseases.